Recognize the Approaches of Critical Thinking of Auditors and Its Representation in the form of Link Analysis(IQA) - Mohammad Poorsamiei; Mohammadreza Abdoli; Hasan Valiyan; Mehdi Safari gerayli (مطالعات تجربی حسابداری مالی, 2021)
Critical thinking in any profession will help the dynamism of that profession to create responsibility. Auditing also requires critical thinking to meet the needs and expectations of stakeholders in the capital market, a thinking that better understands deviant approaches, distortion, and fraud in financial performance, and demonstrates a stronger understanding and intuition against such situations. This research seeks to identify the approaches of critical thinking of auditors and its representation in the form of link analysis. In order to identify the criteria for critical thinking in the profession, systematic search was used on theoretical foundations with the help of accounting experts. Through metasyn thesis analysis, the propositions related to critical thinking in the profession were identified and as a result, the components of analytical capability, inferential capability and intuitive capability were determined as important dimensions in creating critical thinking in the auditing profession. There was a systemic link between connections and impact. The results showed that in order to strengthen the approaches of critical thinking in professional judgments, the existence of technical and specialized knowledge is considered as an important stimulus that gives the auditor results such as improving the level of intuition and the power of mental analysis.